Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/jso.26446
|View full text |Cite
|
Sign up to set email alerts
|

Association of preoperative and postoperative CA72‐4 with gastric cancer outcome

Abstract: Background and Objectives: Carbohydrate antigen 72-4 (CA72-4) is widely used and has been associated with poor prognosis in gastric cancer (GC), but the prognostic significance of elevated preoperative CA72-4 that normalizes after resection remains unknown.Methods: This retrospective cohort analysis was conducted at the Sun Yat-Sen University Cancer Center (SYSUCC). Consecutive patients (n = 1179) with GC who had undergone curative resection for stage Ⅰto Ⅲ gastric adenocarcinoma. The patients were grouped int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…As expected, the 28 genes were strongly associated with tumour immune-in ltrating cells. In addition, C3 (25), CSFR(26-28), CXCR6 (29)(30)(31), and CXCL3 (32) have been identi ed as immune-related factors, and their misexpression in GC affects prognosis (26,31,33,34). Our GO and KEGG analysis results also suggested that these genes are involved in immunoregulation and tumour progression pathways.…”
Section: Discussionmentioning
confidence: 59%
“…As expected, the 28 genes were strongly associated with tumour immune-in ltrating cells. In addition, C3 (25), CSFR(26-28), CXCR6 (29)(30)(31), and CXCL3 (32) have been identi ed as immune-related factors, and their misexpression in GC affects prognosis (26,31,33,34). Our GO and KEGG analysis results also suggested that these genes are involved in immunoregulation and tumour progression pathways.…”
Section: Discussionmentioning
confidence: 59%
“…As expected, the 28 genes were strongly associated with tumour immune-infiltrating cells. In addition, C3 (23), CSFR (24-26), CXCR6 (27-29), and CXCL3 (30) have been identified as immune-related factors, and their misexpression in GC affects prognosis (24,29,31,32). Our GO and KEGG analysis results also suggested that these genes are involved in immunoregulation and tumour progression pathways.…”
Section: Discussionmentioning
confidence: 59%
“…Wakatsuki Ket al also reported that pN ≥ 14 and preoperative CA19-9 were independent risk factors for ERec (early recurrence within 12 months) after curative gastrectomy in pStage III GC [ 27 ]. A previous study of 1179 GC patients showed that pre- or postoperative CA72-4 was independently associated with shorter OS and RFS [ 28 ]. Consistent with previous findings, our study also suggested that lymph node metastasis was a risk factor for recurrence in GC patients.…”
Section: Discussionmentioning
confidence: 99%